Effect of stifle flexion on the position of the cranial tibial artery relative to the proximal tibia in dogs. Issue 8 (4th October 2020) - Mullins, Ronan A.; Escribano Carrera, Antía; Espinel Rupérez, Jorge; Bresciani, Luca; Arthurs, Gareth I.; Hoey, Seamus
Abstract: Objective: To determine the effect of stifle flexion on the proximity of the cranial tibial artery to the proximal tibia in canine stifles with an intact or transected cranial cruciate ligament (CCL). Study design: Ex vivo randomized blinded computed tomographic angiographic study. Sample population: Fifteen pelvic limbs from eight greyhound cadavers. Methods: The femoral artery and vein were cannulated and injected with 10 mL of iohexol. Each limb was placed in lateral recumbency on an acrylic sheet with predrawn femoral and tibial lines representing angles of stifle extension. Computed tomography was performed before (limbs 1‐15) and after (limbs 10‐15) CCL transection. The shortest distance between the cranial tibial artery and proximal tibia (dCrTA‐PT) was measured at a distance of one patellar length from medial intercondylar tubercle. Results: Median dCrTA‐PT in intact specimens at 70°, 90°, 110°, and 135° was 2.04, 2.05, 2.28, and 2.51 mm, respectively ( P = .008). Pairwise comparisons identified a difference between 70° and 135° ( P = .007). Mean dCrTA‐PT in transected specimens at 70°, 90°, 110°, and 135° was 2.60, 2.57, 2.90, and 2.79 mm, respectively ( P = .208). Median overall dCrTA‐PT was 2.24 mm in intact specimens (limbs 1‐15, all four angles of extension combined) and 2.76 mm in transected specimens (limbs 10‐15, all angles combined; P = .01). Conclusion: Flexion of the stifle resulted in a negligible decrease in dCrTA‐PT in intact specimens but had no effect in CCL transected stifles. Clinical significance: The angle of stifle extension does not appear to have any clinically significant effect on the proximity of cranial tibial artery to the proximal tibia.